Fostering Innovation in Prevention and Treatment of Obesity in Youth: Digitally Mediated Physical Play as an Exemplar. Issue 3 (4th February 2021) - Kalarchian, Melissa A.; Hammer, Jessica; Kapuścińska, Adela
Abstract : Novel approaches to obesity prevention among youth are needed. Accordingly, the Office of Women's Health, Department of Health and Human Services, sponsored a challenge to create an interactive video game for obesity prevention. Our team took a theory‐based, evidence‐informed approach to increasing physical activity in girls. Our approach—digitally mediated physical play—allowed us to include computing‐based strategies that promote activity without keeping players in front of a screen. Our prize‐winning prototype app, Frolic, helps girls choose the perfect game to play in any context, engaging parents for support. The app is used to highlight some opportunities and challenges for interdisciplinary collaboration. However, much work remains to be done to deploy innovative digital obesity interventions and fully capture the contributions of these tools. In order to accelerate advances, funding is needed for projects that combine engineering design principles with traditional obesity research paradigms.